DEVELOPMENT OF SOFTWARE FOR DESIGN ONTOLOGICAL REPRESENTATIONS OF PRODUCTION TECHNOLOGIES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The features of the progressive methodological basis for the construction of formalized descriptions of technologies for their subsequent analysis are discussed. The existing possibilities of ontological knowledge engineering applied to the problem of the structural representation of technologies using computer tools are noted. Presented functionality of the developed software that allows automating staged algorithmic procedures for constructing unified decomposition structures of formalized descriptions of technologies. Analysed following development tools: Java Standard Edition programming platform, “Eclipse” IDE, Java programming language, PostgreSQL database management system, “Swing” library for creating a graphical interface and “JGraphX” library for graphs visualization. Database structure of the developed software is described: shown database schema, database tables are defined and the links between them are indicated. The architecture of the developed software is presented: shown data flow scheme and the purpose of each of the modules is described. The main advantages of the developed software “OntoTechnology” is designated, which shows the practical significance of the results.